ANALYZING NEW MEDIA AS PRIMARY HEALTH INFORMATION SOURCES: PATTERNS, RELIABILITY, AND CREDIBILITY USING CROSS-SECTIONAL SURVEY AND REGRESSION ANALYSIS - D., Soundra Rajan; R., Jayaseelan; S., Kadeswaran; K., Muralidharan; K. S., Chithra Lekshmi (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The mounting dependence on new media channels for medical information has reshaped the ways people acquire and handle health knowledge alongside their trust in digital health content. Researchers explore traditional health information-seeking methods following assessment of Internet-based information sources and online health content trustworthiness. Users enrolled in a cross-sectional survey divided into active health seekers by analysis at 56% and passive product discoverers at 44%. Analysis revealed three main reasons why people search for health information where 40% desired clarity about medical conditions and 36% aimed at finding suitable treatments and 30% wanted knowledge about wellness and lifestyle strategies. The study revealed website and mobile application usage was the most common with 50% of participants but social media usage came in second at 30% and forums and blogs gathered the least use at 20%. Regression analysis detected the relation between credible sources and user trust but also demonstrated how users worry about false information and untrusted content. Online health information requires better digital health literacy while integrating trustworthy sources to solve the problem of informational reliability. The obtained data helps researchers better understand today’s changing patterns of medical information consumption and helps develop accurate strategies for digital health knowledge accessibility for the public. Further research needs to study how user engagement with health information changes when algorithms control what content people see.